An overview of occupational noise-induced hearing loss among workers: epidemiology, pathogenesis, and preventive measures - Kou-Huang Chen; Shih-Bin Su; Kow-Tong Chen (Environmental Health and Preventive Medicine, 2020)
Abstract Occupational noise-induced hearing loss (ONIHL) is the most prevalent occupational disease in the world. The goal of this study was to review the epidemiology, pathogenesis, and preventive measures of ONIHL among workers and provide evidence for the implementation of control measures. Literature studies were identified from the MEDLINE, PubMed, Embase, Web of Science, and Google Scholar using the search terms “noise-induced hearing loss” “prevalence”, “pathogenesis”, and “preventive measures”. The articles reviewed in this report were limited from 2000 to 2020. Articles that were not published in the English language, manuscripts without an abstract, and opinion articles were excluded. After a preliminary screening, all of the articles were reviewed and synthesized to provide an overview of the current status of ONIHL among workers. The mechanism of ONIHL among workers is a complex interaction between environmental and host factors (both genetic and acquired factors). The outcomes of noise exposure are different among individual subjects. Clinical trials are currently underway to evaluate the treatment effect of antioxidants on ONIHL. Noise exposure may contribute to temporary or permanent threshold shifts; however, even temporary threshold shifts may predispose an individual to eventual permanent hearing loss. Noise prevention programs are an important preventive measure in reducing the morbidity of ONIHL among workers.